Supplementary Data 1 from Uncoupling CD4+ TIL-Mediated Tumor Killing from JAK-Signaling in Melanoma - Arianna Draghi (15126339) (2025)
CD4+ TILs from melanoma can exert cytotoxic activity against autologous tumor cells (GFP+TCL#17)